The Proposal for a Directive on Copyright in the Digital Single Market : The Reformation of Intermediary Liability in the Platform Economy - Pahta, Kerttu (My University, 2019)
Digitalization has created vast amounts of new business activity, and the market of the 2010’s is full of different kinds of digital services, platforms and social medias. In 2019 the digital market place is very different to the way it was eighteen years ago when the last copyright directive was legislated. Therefore, a reform on copyrights has been required for some time. This renewal has in fact been in the making and the copyright reform was approved by the EU parliament in the Spring of 2019. In this thesis the effects of the proposed Copyright Directive are evaluated, and especially the Article 13 of the proposed Directive (now changed to Article 17), which concerns the obligation of information society service providers to monitor the content on the platforms, uploaded by their users, with the use of filtering technology and to remove copyright infringing material. The thesis analyses critically the copyright reform, as well as the arguments based on which the discussion on the European Commission’s proposal has been built on. In particular, the thesis evaluates the legal solutions the Article 13 offers and whether the Article contributes to the realization of the EU Digital Single Market Strategy. The thesis researches the current status quo of the legislation and the incompatibilities between current and new legislation, the practical issues of Art. 13 and the EU internal market competition issues, i.e. how economic factors affect the successful application of the Article. An emphasis is given to the fundamental and human rights implications of the Article, and the thesis studies how a fair balance is found between the clash of the fundamental rights of the intermediaries, copyright holders and end-users. In the conclusions of this thesis it is stated, that in the light of current developments, the European copyright regulation receives a reform which has been due for a long time, but the realisation of the objectives of the directive and the digital single market is questionable due to the legal and practical problems that are likely to be created by the Article 13.
Keywords: Intellectual Property Law, Copyright, Copyright Directive, E-Commerce Directive, Fundamental Rights, Digitalization, Intermediary Liability, Platform Economy